Polarity of Chemical Bonds in Planar Boron Clusters - Odishvili, Tornike; Chkhartishvili, Levan (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
Boron clusters Bn, in which the number of atoms n £ 20, have a planar or quasi-planar structure in the ground state. Due to their small size, the numbers of differently coordinated central and peripheral atomic sites are comparable, which leads to the polarity of B–B chemical bonds. In the paper, this issue is investigated theoretically – in the model of point static atomic charges. The obtained results may find practical application, since it is quasi-planar boron clusters that play the role of “building blocks” in the growth technologies of borophenes and other promising boron-based 2D-materials.